HUBUNGAN KETAJAMAN PENGLIHATAN DENGAN TINGKAT PENERANGAN RUANGAN PADA ANAK PANTI ASUHAN MUHAMMADIYAH DI KOTA MEDAN - MOHAMAD ILHAM SANDHIKA (LP2MTBM MAKARIOZ, 2021)
Eyes are used to absorb information visually by humans in carrying out various activities. Eyes are used to absorbinformation visually by humans in carrying out various activities. The most common visual problems in developed anddeveloping countries are refractive and blindness disorders. To determine the relationship of visual acuity with the level ofroom lighting in children of the Muhammadiyah Orphanage in Medan City. The type of research used in this study is surveyresearch that is descriptive analytic with quantitative approaches and cross-sectional design. The population of this studywere children in the Muhammadiyah orphanage in Medan City. The technique used is total sampling. The room measured itslevel of information with lux meter. Then the sample was measured with a snellen chart in each room measured by lux meter.Data were tested for normality with the results of p <0.005. Then the Kruskall-walis test was carried out with the result of p =0.000 (p <0.05) so that there was a relationship between the level of illumination of the visual vision. The level of illuminationgreatly affects the vision of an object that can reflect light. The level of luminance will also affect the ability of the eye to seethe object image.